Selective effects of isoflurane on cortico-cortical feedback afferent responses in murine non-primary neocortex. (October 2019) - Murphy, Caitlin; Krause, Bryan; Banks, Matthew
Abstract: Background: General anaesthetics affect loss of consciousness by disrupting information-passing and integration within thalamo-cortical (TC) networks. Feedback cortical connections that carry internally generated signals such as expectation and attention appear more sensitive to anaesthesia than feedforward signals. However, direct evidence for this effect in non-primary cortex is lacking. In addition, direct comparisons between TC core and matrix, and between cortico-cortical (CC) feedforward and feedback responses have not been reported. Methods: We investigated the disruption of synaptic responses by isoflurane of four distinct afferent pathways to non-primary neocortex. We independently activated TC core and matrix and reciprocal CC (feedforward and feedback) pathways using optogenetic techniques, and compared the relative sensitivity of synaptic responses to isoflurane. Results: Under control conditions, activation of axon terminals of all pathways evoked postsynaptic currents (recorded extracellularly) and postsynaptic potentials in pyramidal neurones. CC feedback responses were substantially more sensitive to isoflurane (0 to 0.53 mM) compared with TC core, TC matrix, or CC feedforward pathways. Conclusion: Differential sensitivity of CC feedback synaptic responses to isoflurane in a clinically relevant range suggests a role for disruption of these afferents in the hypnotic effects of anaesthetic agents.